2015
DOI: 10.3846/16484142.2015.1046403
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Current Logistics and Transport Challenges in the Context of the Changing Environment

Abstract: The rapidly changing world determines changes in the business processes. Logistics and transport are the areas facing constant changes. Therefore, an important point is to analyse the current problems of logistics and transport within the context of the changing environment. For many years, the experts of the Dept of Logistics and Transport Management of the Faculty of Transport Engineering from Vilnius Gediminas Technical University have been pursuing research both, in the Baltic Sea Region (BSR) in Lithuania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
15
0
4
Order By: Relevance
“…Similarly, Bose and Pal (2012), Barysiene et al (2015) and Benitez et al (2015) found a strong relationship between a firm's financial performance and green logistics. In addition, ecological practices in logistics operations positively affect a country's GDP per capita ).…”
Section: Fig 3: Plots Of Level Datamentioning
confidence: 87%
“…Similarly, Bose and Pal (2012), Barysiene et al (2015) and Benitez et al (2015) found a strong relationship between a firm's financial performance and green logistics. In addition, ecological practices in logistics operations positively affect a country's GDP per capita ).…”
Section: Fig 3: Plots Of Level Datamentioning
confidence: 87%
“…confirmed that green practices implementation and renewable energy usage in business operations will be the attractions to foreign direct investment inflows. Many Western countries ban the pollutant corporations and impose heavily fines on their polluted vehicles (Barysiene et al 2015). In addition, polluted logistical system also becomes nontariff barrier for companies and decreases the chances of export to European and Western countries (Bolük € and Mert, 2015).…”
Section: Figure 2: Structural Equation Model With Regression Coefficimentioning
confidence: 99%
“…Moreover, connections between machines, devices and elements of the supply chain with shared information will create the possibility of fast modification of orders priorities (on account of customers' requirements or conservation requirements), of monitoring and controlling the productivity of production lines, tracking supplies, as well as streamlining logistic trails (de Sousa Jabbour et al, 2018;Hofmann & Rüsch, 2017). In addition, as Barysienė et al (2015) emphasizes, economic growth in separate sectors of the economy is impossible without transport and logistics companies. Their effective activities generate not only economic but also social benefits.…”
Section: Introductionmentioning
confidence: 99%